2014
DOI: 10.1002/phar.1517
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Multimodal Analgesia with Intravenous Acetaminophen and Opioids in Postoperative Bariatric Patients

Abstract: STUDY OBJECTIVE To evaluate the effect of therapeutic doses of intravenous acetaminophen (IV APAP)on postoperative opioid use following bariatric surgery. DESIGN Retrospective review of medical records. SETTING A 654-bed academic hospital. PATIENTS Records for 104 patients who underwent laparoscopic sleeve gastrectomy (LSG; 44 patients) or laparoscopic Roux-en-Y gastric bypass (LRYGB; 60 patients) were reviewed. Patients received IV APAP 1 g every 6 hours postoperatively (22 LSG patients and 30 LRYGB patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 28 publications
2
25
0
6
Order By: Relevance
“…32e34 Collectively, these factors have raised concerns among perioperative caregivers and spurred the release of recommendations on the use of risk-mitigating strategies including opioid dose reduction and safer analgesic pathways, such as multimodal analgesia. 5 Consistent with previous publications, 35,36 the current analysis demonstrates that, with additional analgesic modes, a gradual decrease in opioid prescription dose is observed. However, the sheer reduction in utilised opioid dose does not per se establish a clinically meaningful benefit of multimodal analgesia unless its utilisation also results in reduced adverse events in the absence of adverse effects attributable to supplemental analgesic techniques.…”
Section: Discussionsupporting
confidence: 90%
“…32e34 Collectively, these factors have raised concerns among perioperative caregivers and spurred the release of recommendations on the use of risk-mitigating strategies including opioid dose reduction and safer analgesic pathways, such as multimodal analgesia. 5 Consistent with previous publications, 35,36 the current analysis demonstrates that, with additional analgesic modes, a gradual decrease in opioid prescription dose is observed. However, the sheer reduction in utilised opioid dose does not per se establish a clinically meaningful benefit of multimodal analgesia unless its utilisation also results in reduced adverse events in the absence of adverse effects attributable to supplemental analgesic techniques.…”
Section: Discussionsupporting
confidence: 90%
“…Cavalcanti et al [9] evaluated the safety of oxycodone for postoperative pain control and found that side effects, including: nausea, dizziness, constipation, and pruritus, occur at significant frequency. Decreasing opioid requirements in surgical patients has also been found to decrease time for return of bowel function as well as hospital length of stay [10,11]. Preoperative narcotic use could lead to an increase in tolerance and require greater amounts of Indicates p values from Fischer's exact test a Reported as mean (±SD) Surg Endosc narcotic to achieve a state of analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Obese bariatric surgical patients receiving postoperative intravenous acetaminophen 1 gram every 6 hours required fewer morphine equivalents [46]. Acetaminophen lowers cumulative narcotic consumption, regardless of the route of administration [47,48]. It has the most favorable effect on blood pressure and should be considered as the first line treatment option in patients with hypertension or cardiovascular disease.…”
Section: Acetaminophenmentioning
confidence: 99%